Protective properties of electromagnetic screens on the basis of iron oer dust and their application for protection of information and people - Козловський, В. В.; Глива, В. А.; Ходаковський, О. В. (Science-based technologies, 2018)
Based on the study of the chemical composition and dispersion of iron ore dust, the feasibility of its use as a filler for the manufacture of composite metal—polymer electromagnetic screens was substantiated. The technology of manufacturing protective shielding materials with guided protective properties has been developed. The protective properties of the developed materials are investigated. It was established that an increase in the dispersion of metal and metal—containing particles by 10—20 times increases the overall coefficient of shielding of a high—frequency electromagnetic field by 6—8 times. In this case, the reflection coefficient of electromagnetic waves is reduced from 0.25 to 0.10. The guaranteed shielding coefficient of the magnetic field of the industrial frequency for the contents of the shielding substance is 12% and is 1.8—2.2. It was found out that the sharp increase of protective properties occurs in the content of the lead substance 11—12%. The dependences of the specific electrical conductivity and dielectric constant on the content and dispersion of the metal and metal—containing substance in the polymer matrix are obtained. These data are the basis for the estimated prediction of the protective properties of electromagnetic screens, depending on the conditions of their use.